An Empirical Study on the Impact of Venture Capital Funding on Founders Financial Returns - Al-Gunaid, Mohammed Abdullah Qasem (2016)
Venture Capital (VC) finding and Initial Public offering (IPO) are amongst the most major financing events for highly growing companies and given also the importance of founders to the entrepreneurial process and the importance of their financial gain from the companies they founded, this research examined the impact that the VC and IPO amounts have on the founders’ financial gain and the imparity of that impact when compared to the effects on the companies as whole. This research selected 48 United States companies that went for an IPO in the year 2013 to be the sample of this empirical study. To select these 48 companies, all 220 companies that went for an IPO in 2013 had to be examined and pick the companies that had VC involvement, had identified individual founders that stayed until the IPO and were United States-based. Those were the only criteria of exclusion that led me to the sample of 48 companies. The results showed that the founders’ financial return has a negative relationship with the VC/IPO ratio but not significant relationship with the absolute amount of VC funding. The results also showed that for VC amount and VC/IPO ratio the impact on founders’ return were different from the impact on companies’ market capitalisation as a whole.